2015
DOI: 10.4236/aim.2015.513092
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mode of Action of <i>Cistus ladaniferus</i> L. Essential Oil Active Fractions on <i>Staphylococcus aureus</i> Strain

Abstract: The purpose of this study was to investigate the primary mode of action of Cistus ladaniferus essential oil active fractions on Staphylococcus aureus strain ATCC6538P (CIP 53.156). The mode of inhibition of the active fractions was assessed by determining the minimum inhibitory concentration (MIC). The effects of time on cell integrity were determined by time-kill, bacteriolysis and loss of 260 and 280-nm-absorbing material assays. Measurement of intra-and extracellular ATP was used to evaluate the energy rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The purpose of this study was to investigate the anti-QS properties of 12 EOs on C. violaceum , which are known to exert several antibacterial activities [ 24 , 25 ]. To achieve this goal, we investigated one of the major molecules putatively responsible for the anti-QS activity, finding cis-cis-p- menthenolide was the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to investigate the anti-QS properties of 12 EOs on C. violaceum , which are known to exert several antibacterial activities [ 24 , 25 ]. To achieve this goal, we investigated one of the major molecules putatively responsible for the anti-QS activity, finding cis-cis-p- menthenolide was the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this depletion of the ATP pool following the addition of lipophilic components was observed in other studies. The alcohol fraction extracts of Cistus ladaniferus essential oil have the capacity to vanish the ATPin on Staphylococcus aureus cells, without growing the ATP out (Guinoiseau et al, 2015). More, components like carvacrol, eugenol and cinnamaldehyde inhibit the ATPase activity of Escherichia coli and Listeria monocytogenes (Gill & Holley, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) assays were performed by a rapid INT (piodonitroterazolium chloride, Sigma-Aldrich) colorimetric assay (Guinoiseau et al, 2015). The L. graveolens oil was serially twofold diluted in dimethylsulfoxide (DMSO, Sigma-Aldrich).…”
Section: Minimum Inhibitory Concentration and Minimum Bactericidal Comentioning
confidence: 99%
See 1 more Smart Citation
“…Following experimental research for antistaphylococcal activity, Guinoiseau [143] demonstrated the potential of C. ladaniferus EO and its efficacy against tested strain, ranging from 0.012 mg/mL for acetate fraction to 0.8 mg/mL for EO in coordination with the inhibition zones. These concentrations were much efficient than those reported with C. creticus EO [142].…”
Section: Antibacterial Effect Of Eomentioning
confidence: 99%